信号f(t)=2ε(t+1)-3ε(t-1)+ε(t-2)的波形图为
举一反三
- 已知信号f(t)的波形如图所示,则f(t)的表达式为() A: (t+1)ε(t) B: δ(t-1)+(t-1)ε(t) C: (t-1)ε(t) D: δ(t+1)+(t+1)ε(t)
- 已知f(t)的波形如下图所示,则f(t)的表达式为 A: f(t)=tε(t)-tε(t-1) B: f(t)=tε(t)-(t-1)ε(t-1) C: f(t)=(1-t)ε(t)-(1-t)ε(t-1) D: f(t)=(t+1)ε(t)-(t+1)ε(t+1)
- 已知信号f(t)的波形如图所示,则=() A: 0 B: δ(t)-δ(t-2) C: 2δ(t)+2δ(t-2) D: 2δ(t)-2δ(t-2)
- 已知f(t)的波形如下图所示,则f(t)的表达式为[img=183x135]17869c17a5df3e3.bmp[/img] A: f(t)=(t+1)ε(t)-(t+1)ε(t+1) B: f(t)=tε(t)-(t-1)ε(t-1) C: f(t)=tε(t)-tε(t-1) D: f(t)=(1-t)ε(t)-(1-t)ε(t-1)
- 已知信号f(t)如图所示,其表达式是()[img=268x156]17e0c04ffc82c35.png[/img] A: ε(t)+2ε(t-2)-ε(t-3) B: ε(t-1)+ε(t-2)-2ε(t-3) C: ε(t)+ε(t-2)-ε(t-3) D: ε(t-1)+ε(t-2)-ε(t-3)